A method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation
Through the impact phase change method, the impact of the fly piece is used to generate high temperature and high pressure, and the density and impact speed of the red phosphorus precursor are regulated, which solves the problems of high raw material loss, complex process and high cost in the preparation of black phosphorus nanomaterials, and realizes black phosphorus nanomaterials Low cost, high efficiency preparation and microstructure control of materials.
Patent Information
- Application Number
- CN202211234420.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-20
- Filing Date
- 2022-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing black phosphorus nanomaterial preparation technology has problems such as high raw material loss, complex process, low production efficiency, high cost and uncontrollable microstructure.
The impact phase change method is used to generate instantaneous high temperature and high pressure by regulating the impact speed of the fly plate and the density of the red phosphorus precursor, and the complete phase change and microstructure regulation of the amorphous red phosphorus precursor are achieved, and black phosphorus nanometers are prepared. sheet, monolayer black phosphorene or oligolayer black phosphorene.
The low-cost, low-loss and high-efficiency preparation of black phosphorus nanomaterials is achieved, with a conversion rate of up to 100%. The microstructure control is realized by regulating process parameters, reducing production costs and improving yield and efficiency.
Smart Images

Figure CN115626614B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing black phosphorus nanomaterials through impact phase change with microstructure regulation function, belonging to the technical field of nanomaterial preparation technology. Background Art
[0002] Black phosphorus is a two-dimensional layered semiconductor material with a direct band gap and exhibits strong in-plane anisotropy. Therefore, black phosphorus has excellent and unique optical, electrical, mechanical and other properties, and has broad application prospects. However, in order to realize the wide application of black phosphorus materials in different fields, black phosphorus materials with different structures must be prepared in a targeted manner. Black phosphorus nanomaterials are black phosphorus materials with a size less than 100nm in at least one dimensional direction, and are also the main form of black phosphorus materials that are widely used. There are many types of nano black phosphorus. Nano black phosphorus with different morphologies and structures has different properties. In practical applications, it will be widely used in different fields such as drug nanocarriers, nanosensor films, and composite nanocatalysts according to the morphology and microstructure characteristics. For example, micron-sized black phosphorus nanosheets with a thickness of 5nm can be used as a matrix to prepare black phosphorus-based quantum dot composite materials, and few-layer black phosphorus ene with a two-dimensional size of about 100 nanometers is widely used in black phosphorus-based heterojunction catalysts. Monolayer black phosphorus ene with a two-dimensional size of about 100 nanometers can be used for the preparation of composite thin film nanosensors, and black phosphorus quantum dots with a two-dimensional size of less than 10nm can be anchored on the surface of other two-dimensional materials to form quantum dot catalysts.
[0003] Black phosphorus has a similar structure to graphite, both of which are molecular layered materials bound by van der Waals forces. Therefore, the preparation methods of black phosphorus nanomaterials mostly draw on the preparation methods of graphite nanomaterials and graphene, and often use black phosphorus as a precursor to prepare black phosphorus nanomaterials by subtractive manufacturing methods such as crushing, peeling, and ablation. This type of preparation method often results in waste of raw materials in the pretreatment, preparation, separation and purification process. At present, although with the advancement of science and technology, the output of black phosphorus has gradually increased from grams to kilograms, the preparation is still relatively difficult, and the unit price is still mostly 1,000 to 10,000 yuan / gram due to different crystallization degrees and sizes. It can be seen that the use of the above-mentioned subtractive manufacturing method to prepare black phosphorus nanomaterials, in addition to factors such as complex processes, the cost of raw materials also leads to high preparation costs and low production efficiency. In addition to the above-mentioned subtractive manufacturing methods, the chemical vapor deposition (CVD) method can also be used to prepare black phosphorene films. However, the CVD method has a complex preparation process, strict condition control, and high cost, and it is still difficult to carry out large-scale production. It can be seen that a low-cost, scalable method for preparing black phosphorus nanomaterials that can achieve microstructure regulation by adjusting process parameters is still urgently needed in the fields of black phosphorus material research and application.
[0004] Using flying sheet impact loading to generate instantaneous high temperature and high pressure is a widely used dynamic high pressure loading technology. It uses the shock wave generated by the high-speed impact of flying sheets to act on the material, forming high temperature and high pressure (102 ~10 3 K, 10 2 ~10 3 GPa), and subject the material to complex mechanical effects such as impact compression, shear, friction, and stretching at the mesoscopic and microscopic levels, resulting in physical and chemical changes in the material, thereby preparing new materials. At present, this technology has been successfully used in the preparation of high-pressure phase C3N4 nanopowders, perovskite nanocrystalline powders, graphene powders and other materials. Combined with existing research reports on the use of static high pressure and other technologies to transform red phosphorus into black phosphorus, it can be seen that black phosphorus materials can be prepared by treating cheap and easy-to-prepare red phosphorus materials by impact loading. However, there are currently no reports on the preparation of black phosphorus nanomaterials with controllable microstructures through process parameter regulation and impact phase transformation. Summary of the invention
[0005] In order to overcome the defects of the existing black phosphorus nanomaterial preparation technology, such as high black phosphorus raw material loss, complex process, low production efficiency, high production cost, and uncontrollable microstructure of nano black phosphorus materials, the purpose of the present invention is to provide a method for preparing black phosphorus nanomaterials through impact phase change with microstructure regulation function.
[0006] To achieve the purpose of the present invention, the following technical solutions are provided.
[0007] A method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation, wherein the device used in the method is a device used in a method for preparing graphene by shock wave treatment of dry ice in patent application CN103663439A, wherein the device comprises: a detonator sleeve, an upper end cover, a charge tube (PVC tube), a lower end cover, a flying piece, a positioning ring, a sample box, a copper gasket, a copper liner, a stainless steel core column, a cavity, and a stainless steel base, wherein:
[0008] The bottom of the stainless steel sample box is equipped with a copper lining, and the powder raw material is placed on the bottom of the copper lining. A copper gasket is arranged on the powder raw material. The stainless steel core column is screwed into the stainless steel sample box to hold the copper gasket, so that the copper gasket and the powder raw material are in close contact and pressed into a preliminary blank. A cavity is left on the side of the stainless steel core column and the stainless steel sample box, and the stainless steel sample box is inverted and placed in the circular groove in the stainless steel base;
[0009] A plastic positioning ring is arranged above the stainless steel base, a stainless steel flying piece is arranged above the plastic positioning ring, a plastic lower end cover is arranged above the stainless steel flying piece, a PVC pipe is arranged above the plastic lower end cover, a plastic upper end cover is arranged above the PVC pipe, a round hole is arranged in the center of the plastic upper end cover, and an aluminum detonator sleeve is placed therein; explosive charge is placed at the bottom of the aluminum detonator sleeve, and a detonator is placed on the top, and the detonator is located in the middle above the plastic upper end cover;
[0010] As shown in the schematic diagram of the device, the PVC pipe, the plastic lower end cap and the stainless steel flying piece are bonded, and the explosives are loaded and the detonator is installed. The detonator is used to detonate the explosives to generate shock waves, and the flying piece is driven to impact the sample box to perform shock treatment on the sample.
[0011] The specific steps of the method are as follows:
[0012] (1) selecting red phosphorus micron powder with a purity of more than 98.9% and obtaining an amorphous red phosphorus precursor through pretreatment;
[0013] The pretreatment is screening, ball milling or centrifugation;
[0014] Preferably, the pretreatment is sieving; further preferably, the sieving is sieving the red phosphorus micron powder with an 800-mesh experimental sieve to obtain a large-particle amorphous lamellar structure red phosphorus precursor with a particle size of more than 0.1 μm;
[0015] (2) The red phosphorus precursor prepared in step (1) is uniformly pressed into a stainless steel sample box containing a copper lining in batches, with a density of 45-75%, the sample box is encapsulated, an impact device is assembled, and explosives and detonators are loaded. After the loading is completed, the explosives are detonated by the detonator to generate shock waves, and flying pieces are driven to impact the sample box to perform impact treatment on the sample, and the flying piece impact speed is 1.5-3.0 km / s; the sample box is recovered, and the black powder is taken out, which is the black phosphorus nanomaterial.
[0016] The black phosphorus nanomaterial is a black phosphorus nanosheet, a single-layer black phosphorene or a few-layer black phosphorene;
[0017] Preferably, the detonation velocity of the explosive is 2100m / s to 3200m / s.
[0018] Beneficial Effects
[0019] (1) The present invention provides a method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation effect. The method uses shock waves to act on an amorphous red phosphorus precursor to generate instantaneous high temperature and high pressure, thereby inducing the amorphous red phosphorus precursor to phase change into nano black phosphorus. The method controls the impact pressure intensity and pressure field change characteristics by regulating the flying sheet impact speed and the matching amorphous red phosphorus precursor density, thereby achieving complete phase change of the red phosphorus precursor into nano black phosphorus, with a conversion rate of up to 100%, thereby overcoming the defect that the nano black phosphorus product is difficult to separate in the prior art. At the same time, since there are many types of nano black phosphorus, and nano black phosphorus with different morphologies and structures has different properties, the method can control the complex mechanical action intensity of the shock wave on the black phosphorus material, such as the degree of fragmentation of mechanical impact, the stretching and peeling effect of the rarefaction wave action, and the sublimation and condensation ratio of the material, by regulating the flying sheet impact speed and the matching of the red phosphorus precursor density, thereby achieving microstructure regulation effect, and converting the amorphous red phosphorus precursor obtained after pretreatment into black phosphorus nanosheets, single-layer black phosphorene, or few-layer black phosphorene with microstructure.
[0020] (2) The present invention provides a method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation function. The method uses inexpensive and easily obtainable micrometer-level red phosphorus as a raw material, and utilizes pretreatment to obtain red phosphorus with an amorphous lamellar structure as a precursor. The flying sheet impact loading process parameters are regulated to achieve complete phase change and microstructure regulation of the red phosphorus precursor in one step, thereby obtaining a black phosphorus nanomaterial with a target microstructure. The method has low raw material loss, simple process, high production efficiency, low production cost, and the ability to completely phase change precursors at the gram level. The production scale can be enlarged according to the similarity law, thereby achieving low-cost preparation of black phosphorus nanomaterials and significantly improving the output and efficiency of black phosphorus nanomaterials.
[0021] (3) The present invention provides a method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation function. In the method, the density of the red phosphorus precursor is 45% to 75%, the detonation velocity of the explosive is 2100 to 3200 m / s, and the compaction of the red phosphorus can reduce the pores in the red phosphorus powder in the sample box, thereby preventing the sample box from being damaged by the shock wave, thereby causing contamination or loss of the final product; by regulating the detonation velocity and density, the shock wave attenuation rate and shock temperature can be controlled, thereby indirectly controlling the treatment effect of the shock wave on the black phosphorus powder obtained by the phase change. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The microstructure of the amorphous red phosphorus precursor obtained after pretreatment in Example 1; Figure (a) is a SEM image; Figure (b) is a TEM image, and the inset image is a selected area electron diffraction (SAED) image of the amorphous red phosphorus at that position.
[0023] Figure 2 This is the SEM image of the powder product prepared in Example 1; wherein the scale of Figure (a) is 100 μm, and the scale of Figure (b) is 50 μm.
[0024] Figure 3 This is an AFM image of the powder product prepared in Example 1; the scale of the left image is 20 μm; the right image is the height information corresponding to Line 1 in the left image.
[0025] Figure 4 The XRD patterns of the amorphous red phosphorus and powder product obtained after pretreatment in Example 1 are shown.
[0026] Figure 5 The Raman spectra of the amorphous red phosphorus and powder product obtained after pretreatment in Example 1.
[0027] Figure 6Figure 1 is a microstructure diagram of the powder product prepared in Example 1; Figure (a) is a TEM image; Figure (b) is the HRTEM and SAED images of the corresponding numbered positions in Figure (a); Figures (c) and (d) are energy dispersive X-ray spectra (EDX) images of the powder product prepared in Example 1.
[0028] Figure 7 This is the SEM image of the powder product prepared in Example 2; wherein the scale of Figure (a) is 100 μm, and the scale of Figure (b) is 20 μm.
[0029] Figure 8 This is an AFM image of the powder product prepared in Example 2; the scale of the left image is 500 nm; the right image is the height information corresponding to Line 1 in the left image.
[0030] Fig. 9 This is the SEM image of the powder product prepared in Example 3; wherein the scale of Figure (a) is 50 μm, and the scale of Figure (b) is 10 μm.
[0031] Fig.10 This is an AFM image of the powder product prepared in Example 3; the scale of the left image is 100 nm; the right image is the height information corresponding to Line 1 in the left image. DETAILED DESCRIPTION
[0032] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the present invention.
[0033] Red phosphorus: purity is 98.9%, particle size is 100 mesh, purchased from Aladdin Co. Ltd., size is 0.1-20 μm.
[0034] Explosives: Industrial explosive expanded ammonium nitrate, with an explosion velocity of 2100m / s~3200m / s.
[0035] The following examples were tested as follows:
[0036] X-ray diffraction (XRD) test: D / MAX-2500, Rikagu, Japan.
[0037] Raman spectroscopy test: Horiba LabRAM HR-Evolution, Horiba, Japan.
[0038] Scanning electron microscope (SEM): Hitachi S-4800 and SU8020.
[0039] Transmission electron microscopy (TEM): JEM-2010.
[0040] Atomic force microscope (AFM): Bruker Dimension Icon.
[0041] Density = (sample filling density / red phosphorus theoretical density) × 100%.
[0042] The flying flake impact velocity was measured by laser Doppler velocimetry (PDV) with the instrument model: PDV-10000T.
[0043] The device used in the method is a device used in the method for preparing graphene by shock wave treatment of dry ice as described in patent application CN103663439A, and the device comprises: an aluminum detonator sleeve, a plastic upper end cover, a charge tube (PVC tube), a plastic lower end cover, a stainless steel flyer, a plastic positioning ring, a sample box, a copper gasket, a copper liner, a stainless steel core column, a cavity, and a stainless steel base, wherein:
[0044] The bottom of the sample box is provided with a copper lining, the powder raw material is placed on the top of the copper lining, a copper gasket is provided on the top of the powder raw material, a stainless steel core column is screwed into the stainless steel sample box to hold the copper gasket, so that the copper gasket and the powder raw material are in close contact and pressed into a preliminary blank, a cavity is left on the side of the stainless steel core column and the stainless steel sample box, and the stainless steel sample box is inverted and placed into the circular groove in the stainless steel base;
[0045] A plastic positioning ring is arranged above the stainless steel base, a stainless steel flying piece is arranged above the plastic positioning ring, a plastic lower end cover is arranged above the stainless steel flying piece, a PVC pipe is arranged above the plastic lower end cover, a plastic upper end cover is arranged above the PVC pipe, a round hole is arranged in the center of the plastic upper end cover, and an aluminum detonator sleeve is placed therein; explosive charge is placed at the bottom of the aluminum detonator sleeve, and a detonator is placed on the top, and the detonator is located in the middle above the plastic upper end cover;
[0046] The PVC pipe and the plastic lower end cover are bonded together, the stainless steel flying piece is bonded in the circular groove of the plastic lower end cover, the explosive is loaded into the PVC pipe, the detonator is inserted into the top center of the transfer charge, and the detonator is detonated for explosion impact treatment.
[0047] Example 1
[0048] A method for preparing black phosphorus nanosheets by impact phase change with microstructure regulation, the method comprising the following specific steps:
[0049] (1) sieving 10 g of red phosphorus powder, and manually sieving out large particles with a particle size of 0.1 μm or more from the red phosphorus powder using an 800-mesh experimental sieve to obtain an amorphous lamellar structure red phosphorus precursor;
[0050] The microscopic morphology of the red phosphorus precursor obtained after sieving pretreatment was characterized. Figure 1As shown, Figure (a) shows that there is a lamellar structure with a lateral size of about 5 μm in the red phosphorus precursor, and Figure (b) shows that there is also a small-sized lamellar structure with a lateral size of about 0.4 μm in the precursor red phosphorus. The selected area electron diffraction pattern embedded in Figure (b) shows that the red phosphorus precursor is an amorphous structure.
[0051] (2) Place 2.0 g of the red phosphorus precursor obtained in step (1) into a copper-lined stainless steel sample box in the apparatus and compact it to achieve a sample sealing state. The sample packing density is 1.18 g / cm 3 The theoretical density of red phosphorus is 2.34 g / cm 3 The density of amorphous red phosphorus is 50.42%; 500g of industrial explosive expanded ammonium nitrate is placed in the PVC tube outside the stainless steel sample box, the diameter of the cartridge is 75mm, and the explosive is detonated by a detonator to generate a shock wave, and drive the flying pieces to impact the sample box. The flying piece impact speed is measured by the PDV system to be 1.5km / s, and the sample is subjected to impact treatment; after the experiment, the sample box is recovered to obtain a black powder product.
[0052] The powder product prepared in Example 1 was characterized by SEM, and the results were as follows: Figure 2 As shown, the obtained product is flat in the form of wrinkled nanosheets; since liquid phosphorus cannot transform into black phosphorus, the lateral size of the powder product is consistent with that of red phosphorus, indicating that the red phosphorus did not liquefy during the phase change, and the impact phase change was a solid-solid phase change. The microscopic morphology and structure of the product are the same as those of the reactants, and there is no obvious change in size.
[0053] The powder product prepared in Example 1 was characterized by SEM and AFM microstructures. Figure 2 , 3 As shown, the black phosphorus nanomaterial in the product is a large-sized nanosheet with a lateral size of 10μm to 50μm and a thickness of about 20nm.
[0054] The amorphous red phosphorus and the product powder obtained after the pretreatment in Example 1 were subjected to phase and microstructure analysis. Figure 4 It can be seen that the XRD diffraction peak corresponds to the black phosphorus JCFDS card 73-1358, which confirms that the prepared powder product is black phosphorus with an orthorhombic structure; the reactant amorphous red phosphorus is a red powder, and the powder products prepared in Example 1 are all black powders, and the XRD spectrum of the powder product prepared in Example 1 contains only one phase of black phosphorus, without red phosphorus or other impurities, indicating that the method converts all amorphous red phosphorus into nano black phosphorus, achieving a conversion rate of 100%. Figure 5 It can be seen that the Raman spectrum of amorphous red phosphorus is at 353 cm -1There is a Raman scattering peak. According to the description of the Raman spectrum of black phosphorus in the literature, it can be known that the Raman characteristic peaks of black phosphorus are located at 362.5cm -1 , 439.3cm -1 , 467.6cm -1 , corresponding to the out-of-plane vibration A g 1 Mode, in-plane vibration in zigzag direction B 2g Mode and in-plane vibration in the armchair direction A g 2 The prepared powder product has a typical black phosphorus scattering peak, which is consistent with the XRD results, indicating that the obtained powder product is black phosphorus.
[0055] The powder product prepared in Example 1 was subjected to TEM test. Figure 6 As shown, the results prove that the product is a crystal with an orthorhombic structure, and the lattice spacing is 0.210nm, 0.224nm, and 0.256nm, respectively corresponding to the corresponding black phosphorus crystal planes (131), (041), and (111). The EDX results show that the product is phosphorus without other impurity elements. The above tests prove that the powder product prepared in Example 1 is a black phosphorus nanosheet with an orthorhombic structure, and the product has high purity and is not degraded by other factors such as oxygen and water in the air.
[0056] Example 2
[0057] A method for preparing a few-layer black phosphorus nanosheet by impact phase change with microstructure regulation, the method specifically comprises the following steps:
[0058] (1) sieving 10 g of red phosphorus powder, and manually sieving out large particles with a particle size of 0.1 μm or more from the red phosphorus powder using an 800-mesh experimental sieve to obtain an amorphous lamellar structure red phosphorus precursor;
[0059] (2) Place 2.0 g of the red phosphorus precursor obtained in step (1) into a copper-lined stainless steel sample box in the apparatus and compact it to achieve a sample sealing state. The sample packing density is 1.18 g / cm 3 The theoretical density of red phosphorus is 2.34 g / cm 3 The density of amorphous red phosphorus is 50.42%; 700g of industrial explosive expanded ammonium nitrate is placed in the PVC tube outside the stainless steel sample box, the diameter of the cartridge is 90mm, and the explosive is detonated by a detonator to generate a shock wave, and drive the flying pieces to impact the sample box. The flying piece impact speed is measured by the PDV system to be 2.3km / s, and the sample is subjected to impact treatment; after the experiment, the sample box is recovered to obtain a black powder product.
[0060] The powder product prepared in Example 2 was characterized by SEM and AFM microstructures, and the results were as follows: Figure 7 and Figure 8 As shown, the black powder product is a few-layer black phosphorus nanosheet with a lateral size of 5 μm to 20 μm and a thickness of about 5 nm.
[0061] Example 3
[0062] A method for preparing a few-layer black phosphorene by impact phase change with microstructure regulation, the method comprises the following specific steps:
[0063] (1) sieving 10 g of red phosphorus powder, and manually sieving out large particles with a particle size of 0.1 μm or more from the red phosphorus powder using an 800-mesh experimental sieve to obtain an amorphous lamellar structure red phosphorus precursor;
[0064] (2) Place 2.0 g of the red phosphorus precursor obtained in step (1) into a copper-lined stainless steel sample box in the apparatus and compact it to achieve a sample sealing state. The sample packing density is 1.18 g / cm 3 The theoretical density of red phosphorus is 2.34 g / cm 3 The density of amorphous red phosphorus is 50.42%; 1000g of industrial explosive expanded ammonium nitrate is placed in a PVC tube outside a stainless steel sample box, the diameter of the cartridge is 100mm, and a detonator is used to detonate the explosive to generate a shock wave, and drive the flying pieces to impact the sample box. The flying piece impact speed is measured by the PDV system to be 3.0km / s, and the sample is subjected to impact treatment; after the experiment, the sample box is recovered to obtain a black powder product.
[0065] The powder product prepared in Example 3 was characterized by SEM and AFM microstructures. The results were as follows: Fig. 9 and Fig.10 As shown, the black powder product is a few-layer black phosphorene with a lateral size of 1 μm to 20 μm and a thickness of about 1.7 nm.
Claims
1. A method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation, characterized in that: (1) selecting red phosphorus micron powder with a purity of more than 98.9% and obtaining an amorphous red phosphorus precursor through pretreatment; The pretreatment is screening analysis; (2) Pressing the red phosphorus precursor into a stainless steel sample box of an impact device in batches to a density of 45 to 75%, sealing the sample box, assembling the impact device, and loading the explosive and detonator; After the charge is loaded, the explosive is detonated by a detonator to generate a shock wave, driving the flying pieces to impact the sample box, and the sample is subjected to impact treatment, and the flying pieces have an impact speed of 1.5 to 3.0 km / s; the sample box is recovered, and the black powder is taken out, which is the black phosphorus nanomaterial; the black phosphorus nanomaterial is a black phosphorus nanosheet, a single-layer black phosphorene, or a few-layer black phosphorene; The impact device is provided with a base, a positioning ring, a flying piece, a lower end cover, a PVC pipe and an upper end cover in order from bottom to top. The PVC pipe and the lower end cover are bonded together, the flying piece is bonded in the circular groove of the lower end cover, and a detonator sleeve is installed in the central circular hole of the upper end cover. The explosive is loaded into the PVC pipe, the detonator is inserted into the top center of the explosive at the bottom of the detonator sleeve, and the detonator is detonated to perform an explosion impact treatment; The bottom of the sample box is provided with a copper lining on the bottom for placing the powder raw material, a copper gasket is provided above the powder raw material, a stainless steel core column is screwed into the stainless steel sample box and a cavity is left on the side, and the stainless steel sample box is inverted and installed in the circular groove of the base; The detonation velocity of the explosive is 2100-3200 m / s.
2. The method for preparing black phosphorus nanomaterials by impact phase change with microstructure regulation according to claim 1, characterized in that: The sieving is to sieving the red phosphorus micron powder with an 800-mesh experimental sieve to obtain an amorphous lamellar structure red phosphorus precursor with a particle size of more than 0.1 μm.
Citation Information
Patent Citations
Method and device for preparing graphene through processing dry ice by shock waves
CN103663439A